PENGARUH LATIHAN BALL FELLING DAN AGILITY TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PERMAINAN FUTSAL ESTRAKULIKULER FUTSAL PUTRA - Putri, Adinda; Muhammad Idris; Jujur Gunawan Manullang (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine whether there is an effect of ballfelling and agility training on the ability to dribble the ball in extracurricular futsal games for boys at SD Negeri 3 Sembawa. This study is a type of quantitative research using an experimental research method, namely in the form of One-Group Pretest - Posttest - Design, namely this design has a pretest, before being given treatment. The subjects of this study were all students participating in the extracurricular futsal for boys at SD Negeri 3 Sembawa, totaling 20 students. The data analysis technique used the T-Test Technique calculation analysis, namely the average pretest and average. The population of this study was 31 students. The sample taken was 20 extracurricular futsal students. In sampling using saturated sampling. The results of the research data show that the mean pretest for the ability to dribble the ball for boys is 6.6630. While the mean posttest for the ability to dribble the ball is 5.5. Data analysis in this study using the t-test analysis that has been carried out obtained t count 7.139> t table 1.686. So it can be concluded that Ha is accepted and Ho is rejected, so the hypothesis states that there is an influence of ball dribble and agility training on the ability to dribble the ball in extracurricular futsal games for boys at SD Negeri 3 Sembawa.